Early Childhood Cognitive Development Through Games Educational Tool - Suprayitno Sutoyo (Bina Nusantara University, 2017)
Games Educational Tool are all things that can be used as a medium to play that have educational value, one of the benefits is that it helps the growth of all aspects of physical and cognitive abilities. This study will explain how the media has a very important role in stimulating the growth of a child's brain. Using descriptive qualitative method to determine the cognitive educational element in the game. The results of this study to prove that media educational games have a major role in the cognitive abilities of children floating.